Three vs. Four Cycles of Neoadjuvant Chemotherapy for Localized Muscle Invasive Bladder Cancer Undergoing Radical Cystectomy: A Retrospective Multi-Institutional Analysis - Ferro, Matteo; de Cobelli, Ottavio; Musi, Gennaro; Lucarelli, Giuseppe; Terracciano, Daniela; Pacella, Daniela; Muto, Tommaso; Porreca, Angelo; Busetto, Gian Maria; Del Giudice, Francesco; Soria, Francesco; Gontero, Paolo; et al. (Frontiers in Oncology, 2021)
Background. Three or four cycles of cisplatin-based chemotherapy is the standard neoadjuvant treatment prior to cystectomy in patients with muscle-invasive bladder cancer. Although NCCN guidelines recommend 4 cycles of cisplatin-gemcitabine, three cycles are also commonly administered in clinical practice. In this multicenter retrospective study, we assessed a large and homogenous cohort of patients with urothelial bladder cancer (UBC) treated with three or four cycles of neoadjuvant cisplatin-gemcitabine followed by radical cystectomy, in order to explore whether three vs. four cycles were associated with different outcomes. Methods. Patients with histologically confirmed muscle-invasive UBC included in this retrospective study had to be treated with either 3 (cohort A) or 4 (cohort B) cycles of cisplatin-gemcitabine as neoadjuvant therapy before undergoing radical cystectomy with lymphadenectomy. Outcomes including pathologic downstaging to non-muscle invasive disease, pathologic complete response, overall- and cancer-specific- survival as well as time to recurrence were compared between cohorts A vs. B. Results. At univariate analysis, the number of neoadjuvant cycles was not associated with either pathologic complete response, pathologic downstaging, time to recurrence, cancer specific, and overall survival. Of note, patients in cohort B vs. A showed a worse non-cancer specific overall survival at univariate analysis (HR= 2.53; 95 CI= 1.05 - 6.10; p=0.046), although this finding was not confirmed at multivariate analysis. Conclusions. Our findings suggest that 3 cycles of cisplatin-gemcitabine may be equally effective, with less long-term toxicity, compared to 4 cycles in the neoadjuvant setting.